Studi BRT Koridor Antar Kampus di Kota Semarang - Qudus, Firdaus Amalul; Aditama, Putra; Ismiyati, Ismiyati; Narayudha, Moga (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2017)
The public transportation in Semarang City which less of services and comfort made the students don?t use it. Based on the problem, it makes the idea of bus rapid transit Inter campuses created. Bus rapid transit expected to be a solution of the transportation needs of students and the other people around colleges, it also expected to make a communication Inter student colleges in Semarang City.The purposes of this study is to analyze the route of BRT, amount of BRT, bus stop, and the cost of BRT Inter campuses. quantitative approach metodology used to analyze the BRT performances dan qualitative approach for the people responses. The cost determine with component analyze method. From the result of the study of bus rapid transit inter colleges the length of route 36 km, and passes 21 colleges obtained. The cost simulated with comparison number of passengers. The calculation cost of bus rapid transit Rp 2.633,994 is about to loss if 70% of passengers is common passengers. For common passengers the cost is Rp 3.500 and 1.000 for school student passengers. The Government should provide feeder for the unserved collegeKata kunci : transportation, bus rapid transit, route, cost